The relationship between bitcoin and the stock market: empirical evidence from the ASEAN countries - Le, Ha Duong (2025)
This dissertation examines the relationship between Bitcoin returns and the stock market performance of selected ASEAN countries over a 6-year period, from July 2018 to June 2024, using the Dynamic Conditional Correlation Generalized Autoregressive Conditional Heteroskedasticity (DCC-GARCH) model. With the increasing prominence of Bitcoin and its potential influence on traditional financial markets, this study aims to explore the correlation between Bitcoin's volatility and returns with the stock market performance of ASEAN nations, including Vietnam, Indonesia, Malaysia, Singapore, Thailand, and the Philippines.